Status dan Perkembangan Proyek Loon Terkini [Present Status and Development of Loon Project] - Diah Yuniarti; Hilarion Hamjen (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2017)
Studi ini dilakukan untuk memperoleh gambaran terkait status dan perkembangan Proyek Loon di berbagai negara saat ini dari berbagai aspek hingga awal tahun 2017. Studi ini menggunakan pendekatan kualitatif dan studi literatur. Hasil penelitian menunjukkan bahwa setelah Google melakukan trial Loon di Selandia Baru, Brazil, dan Australia, saat ini Proyek Loon masih mengusahakan uji coba dan komersialisasi di negara-negara Asia yaitu di India, Sri Langka dan Indonesia terutama negara dengan banyak penduduk di wilayah terpencil yang masih belum mendapatkan layanan telekomunikasi. Dalam perjalanannya, uji coba dan komersialisasi Proyek Loon di beberapa negara tersebut terkendala beberapa hal, terutama perizinan, baik lisensi frekuensi maupun perizinan ruang udara. *****This study is conducted to gather illustration related to recent status and development of Project Loon in different countries viewed from various aspects by the beginning of 2017. The study is using qualitative approach and literature studies. Research result shows that after Google conducted Loon trials in New Zealand, Brazil and Australia, currently Project Loon is still exploring trial and commercialization in Asia countries which are India, Sri Langka and Indonesia, particularly in country which has many underserve population of telecommunication services in remote areas. On its way, trial and commercialization of Project Loon in those different countries are constrained by several issues, particularly in term of whether frequency license or airspace permissions.